Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, Dan Motivasi Kerja Terhadap Kinerja Karyawan PT Mega Trans Medan - Endang Haryati; Metya Lutviani; Asmaul Husna; Fahmi Sulaiman (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The company was founded to provide welfare for stakeholders, namely those who are involved in company activities, either directly or indirectly. Those who are prioritized in obtaining welfare for the results provided by the company are shareholders, the board of directors, employees, including the government and the community. This is the main purpose of establishing the company. Companies engaged in any field, including manufacturing companies, trading companies, and service companies, still have the same goal, namely to improve the welfare of stakeholders. Identification of problems, namely (a) Employee performance which has decreased from the last 3 years (b) Lack of employee trust in company leaders as indicated by a lack of employee motivation at work (c) Some employees do not have a strong motivation to get awards or achievements (d) Environment company work that is not good for employees. The purpose of this study was to determine the effect of leadership style, work environment and work motivation on the performance of employees of PT. Mega Trans Medan. This research is a quantitative correlational type to see the effect between variables and the research was conducted on several employees by distributing questionnaires. Leadership style has a significance value of 0.000 <0.05 and a t value of 9.9419 > 2.0106, so the conclusion is, Ho is rejected, meaning that there is a significant influence between leadership style and employee performance. The work environment has a significance value of 0.803>0.05 and a t-count value of 0.251 <2.0106, so the conclusion is, Ho is accepted, meaning that there is no significant effect between the work environment and employee performance. Work motivation has a significance value of 0.02 <0.05 and a t value of 2.401 > 2.0106, so the conclusion is, Ho is rejected, meaning that there is a significant influence between work motivation and employee performance. From the results of data processing, obtained a significance value of 0.000 which is smaller than 0.05. From this analysis, Ho is rejected, meaning that there are simultaneously independent variables affecting the dependent variable. To improve employee performance, PT. Trans Mega Medan must improve leadership style, work environment and work motivation. The value of Adjusted R Square in the table above is 0.741 or 74.1%. This condition explains that 74.1% leadership style, work environment and work motivation have a significant effect on employee performance. The remaining 35.9% is influenced by other variables not examined in this study.